FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN MEMBACA SISWA (STUDI KASUS DI SDN 105 PEKANBARU) - Ade Irma Suryani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Reading is very important for life because reading can make us know all the information we need. Students are able to read not by chance or by inspiration, but because they are taught. Reading is not a natural activity, but a set of components that are mastered privately and gradually, which are then integrated and become automatic. However, at present there are still problems with reading in primary schools, namely the lack of students' reading skills in high grades. This research is motivated by the low reading ability of fifth grade students at SDN 105 Pekanbaru. There are 2 students who became the object of this study because of their lack of reading ability compared to their other friends. In connection with these problems, researchers conducted a study of fifth grade students at Pekanbaru Elementary School 105 with the aim of knowing what factors influenced students' reading ability. This type of research is descriptive qualitative with the method used is the survey and observation methods. Data collection conducted in this study was by interview and documentation as supporting material. Based on the results of data analysis obtained from the triangulation of data collection observations and interviews conducted by researchers of this study concluded that the factors affecting reading ability of students in SD Negeri 105 Pekanbaru are intellectual factors and psychological factors.